Ukuran Perusahaan, Profitabilitas, Likuiditas, Pertumbuhan Laba Dan Kualitas Laba Pada Perusahaan Pertambangan Di Indonesia - Teguh Erawati; Sisilia Stefani Wuarlela (Jurnal Literasi Akuntansi, 2022)
Purpose: This study aims to prove the effect of firm size ,profitability, liquidity and earnings growth on earnings quality.the research sample is mining companies listed on the indonesia stck exchange (IDX) in 2017-2020 using purposive sampling. Method: sampling used sampling method and produced 80 sample data. Data analysi technques wit multiple linier analysis Finding:  this study shows that firm size has no significant effect on earnings quality,profitability has a significant effect on earnings quality,liquidity has asignificant offect on earnings quality and earning rowth has no significant effect on earning quality. Novelty: The implications of this research are relted to earning quality.other financial statement informasion needs to the quality of earnings in the company.this shows that users of financial statements,especially investor, need to consider the liquidity factor when making decisions for invertors in affiliated companies